2018
DOI: 10.1287/orsc.2018.1225
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Learning and Overconfidence on Entrepreneurial Entry and Exit

Abstract: Empirical evidence suggests that entrepreneurs make mistakes: too many enter markets and, once there, persist too long. Although scholars have largely settled on behavioral bias as the cause, we suggest that this consensus is premature. These mistakes may also arise from a process in which entrepreneurs continually learn about their prospects and make entry and exit decisions based on what they have learned. We develop a computational model of this process that connects pre- and post-entry learning and can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 79 publications
2
55
0
Order By: Relevance
“…Also, as stated earlier in the paper, prior research related to pre-entry learning (Chen et al, 2018;Fong and Nisbett, 1991;Ivernizzi et al, 2017) indicates that certain decision biases of entrepreneurs as well as the effect of their overconfidence can be mitigated through pre-entry learning and budgeting. While it may not be desirable to overburden an entrepreneur with exhaustive due diligence, it may be possible to provide a reasonable project management checklist or sample legal questions that must be answered, with the answers available on the fundraising page for the project.…”
Section: Nejementioning
confidence: 59%
See 3 more Smart Citations
“…Also, as stated earlier in the paper, prior research related to pre-entry learning (Chen et al, 2018;Fong and Nisbett, 1991;Ivernizzi et al, 2017) indicates that certain decision biases of entrepreneurs as well as the effect of their overconfidence can be mitigated through pre-entry learning and budgeting. While it may not be desirable to overburden an entrepreneur with exhaustive due diligence, it may be possible to provide a reasonable project management checklist or sample legal questions that must be answered, with the answers available on the fundraising page for the project.…”
Section: Nejementioning
confidence: 59%
“…For example, as Fong and Nisbett (1991) noted, decision biases can be corrected through training. Chen et al (2018) characterized entrepreneurship as the unfolding feedback-learning process and their model indicated that pre-entry learning activities have substantial positive implications for the entry decision and varying the length and quality of pre-entry learning shows how experience remedies certain biases, though not all bias. Similarly, Ivernizzi et al (2017) suggest that entrepreneurs' overconfidence can be mitigated by their level of educational attainment and the use of budgetary controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this task, multiple alternatives exist, and an agent learns its values through repeated choices [3]. is model has been used extensively in organization science to analyse learning by doing processes, including individual-level processes [31], coupled learning process between individuals (or organizations) [24], and organization-level adaptation [25]. Along with a formal definition, we provide a numerical illustration of SCBB.…”
Section: Formal Definitionmentioning
confidence: 99%